The Relationship between Leukocytosis and Hyponatremia with Mortality Ischemic Stroke Patients - Futana, Ninda Pradani; Sulistyani, S; Setiawan, Iwan; Djatmiko, Safari Wahyu (Universitas Muhammadiyah Surakarta, 2024)
Background: Ischemic stroke is the cause of increased mortality in the world, especially in developing countries. Ischemic stroke is caused by a decrease in blood flow and oxygen supply in the brain. Increased leukocyte count as an inflammatory response, as well as impaired sodium levels in the form of hyponatremia, can worsen the patients condition and increase the risk of death. Leukocytosis after ischemia causes inflammation of neurons and continuous brain injury. Leukocyte infiltration can also increase obstruction causing oxygen levels to decrease. Hyponatremia which associated with cerebral salt wasting (CSWS), Syndrome of inappropriate antidiuretic hormone (SIADH), cerebral edema and increased intracranial pressure also increases the risk of death for ischemic stroke patients. Purpose: The purpose of this study is determine the relationship between leukocytosis and hyponatremia with the morality of ischemic stroke patients. Methodology: The method used in this study is a cross sectional. Sampling was carried out using non-randomized sampling and obtained 61 patients with a diagnosis of ischemic stroke and recorded completely in medical reports from 2022 to 2024 at RSUD dr soeratno Gemolong. Statistical analysis used was chi square for bivariate and logistic regression for multivariate. Results: The results obtained a significant p value in leukocytosis of 0.007 and hyponatremia of 0.008. The results of multivariate analysis obtained significant values in both variables with p< 0.05. Applications: In this research that shows an association between leukocytosis and hyponatremia with ischemic stroke mortality can be used further for researchers and clinicians, especially in the health fields.